Implementasi Program Makan Bergizi Gratis Pada Pemerintahan Prabowo-Gibran: Solusi dan Tantangan - Pora, Sahrul; Muksin, Dafrin; Rahmat, Al Fauzi (Universitas Muhammadiyah Sorong, 2025)
This research examines the implementation of the free nutritious meal program. The aim is to find out the content of this program and its implementation in the field. The method used is qualitative research with a descriptive approach. Data was obtained through various online media, ministry websites, and other documents. The results showed that the free nutritious meal program was implemented on January 6, 2025. This program aims to improve human resources, reduce stunting rates, and increase student learning motivation. The targets are students, toddlers, and pregnant women. The implementation of the free nutritious meal program faces challenges in communication, resources, executor disposition, and bureaucratic structure. The government has conducted extensive socialization with various media platforms and in person, but remote areas still experience problems accessing digital information. In terms of resources, the large budget allocation has not been fully matched by infrastructure readiness, causing constraints in distribution. The disposition of implementers also plays an important role, with support from lower-level implementers. However, cases of rejection in some areas show the need for increased readiness in the field